Analysis of biochemical and bioactive content of red rice cv Sidikalang through gamma ray irradiation induction (M4) - Parlindungan Lumbanraja; Dunan Naibaho; Susana Tabah Trina Sumihar; Ferlist Rio Siahaan (Indonesian Journal of Agricultural Research, 2026)
Red rice derives its characteristic color from anthocyanin pigments located in the pericarp and outer endosperm layers, which contribute to its biochemical and bioactive properties. Gamma-ray irradiation is widely applied as a mutation induction technique to enhance genetic variability and improve functional traits in crop plants. This study aimed to evaluate the biochemical and bioactive content of the red rice cv Sidikalang following gamma-ray irradiation. The experiment was conducted at the Central Laboratory, Faculty of Agriculture, Universitas Sumatera Utara, from October 2024 to February 2025, using a single-factor Randomized Block Design with irradiation doses of 0, 200, 400, and 600 Gy and three replications. Biochemical and bioactive parameters analyzed included carbohydrate, protein, fat, vitamin A, fiber, ash, water content, and anthocyanin. The results showed that gamma-ray irradiation had no significant effect on protein, fat, vitamin A, and carbohydrate content, but significantly affected water content, fiber, ash, and anthocyanin. Irradiation doses of 200-600 Gy resulted in significantly higher fiber and anthocyanin content compared to the control. These findings indicate that gamma-ray irradiation has the potential to enhance specific functional and nutritional traits of red rice, providing valuable insights for mutation breeding programs aimed at developing nutritionally improved rice varieties.